ANALYSIS OF LEADING SECTOR LINKAGES IN THE PURWOMANGGUNG AREA - Siti Rikhanatul Ummah; Edy Yusuf Agung Gunanto (Universitas Tidar, 2023)
This study intends to identify the linkages of leading sectors to the economy in the Purwomanggung area, Central Java. Secondary data for the period 2012-2021 was collected from the Central Statistics Agency (BPS) of Central Java, as well as BPS for each district/city in the Purwomanggung area. In this study, analysis of Shift Share, Moran's Index, and LISA is used. The dominant leading sectors owned by districts/cities in the Purwomanggung area are the agricultural sector, the construction sector, and the wholesale and retail trade sector. There is a spatial correlation in the results of spatial linkages based on the leading sector that dominates with a high scale of regional observation and is surrounded by a nearby environment that has a high scale (High-High), a high regional observation value and is surrounded by a nearby environment of lower value ( High-Low), a low area observation value surrounded by a nearby environment with a higher value (Low-High), and a low area observation value surrounded by a low-value nearby environment (Low-Low). The results of linear regression analysis demonstrate which sectors have a substantial impact on growth. The wholesale and retail trade sector is another regional economy with the largest geographical links. While the agriculture and construction sectors have a considerable impact on economic growth in other areas.